PHQ‐9 and SNOT‐22: Elucidating the Prevalence of Depression in Chronic Rhinosinusitis. (12th November 2019) - Vandelaar, Laura J.; Jiang, Zi Yang; Saini, Alok; Yao, William C.; Luong, Amber U.; Citardi, Martin J.
Abstract : Objective: Chronic rhinosinusitis (CRS) has been associated with comorbid depression, yet the prevalence of depression among all patients with CRS is not well described. The Patient Health Questionnaire–9 (PHQ‐9), a validated instrument for diagnosing depression, has been used to assess depression in a variety of clinical settings. PHQ‐9 scores ≥10 are the threshold for a depression diagnosis. The purpose of this study was to assess the prevalence of depression in a rhinology practice and compare the PHQ‐9 with the 22‐item Sinonasal Outcome Test (SNOT‐22). Study Design: Retrospective chart review. Setting: Tertiary rhinology practice. Subjects and Methods: During the 2‐month period ending April 30, 2018, all rhinology patients were asked to complete the PHQ‐9 and SNOT‐22. Results: Among 216 patients, 46 (21.3%) had a self‐reported history of depression, and 39 (18.1%) had a PHQ‐9 score ≥10. Of the 39 patients screening positive for depression, 18 (41.9%) had no history of depression. Comparison of PHQ‐9 with overall SNOT‐22 score had a Pearson's coefficient of 0.632 ( P <. 005). Logistic regression showed that the highest 2 quintiles of SNOT‐22 scores had an odds ratio of 60.6 (95% CI, 9.7‐378.3) for a positive depression screen (PHQ‐9 score ≥10). Conclusion: Depression rates (estimated by PHQ‐9 responses) among rhinology patients are similar to chronic disease populations; depression may be underdiagnosed in rhinology patients. Higher SNOT‐22 scores were associated with higher PHQ‐9 scores. Further studies are warranted to understand the impact of comorbid conditions of depression and CRS in patient quality of life.